A new species of the genus Ectagela Schmidt from Iran (Hemiptera, Heteroptera, Miridae, Phylinae) - Hosseini, Reza; Shamsi, Mohsen (Zootaxa, 2014)
A new species of the genus Ectagela Schmidt (Phylinae) from Iran, Ectagela kermanensis sp. nov. is described and illustrated. The type specimens are deposited in the insect collection of the Natural History Museum of University of Guilan, Rasht, Iran.